EVALUATION OF THE EFFECTIVENESS OF FINANCIAL CONTROL SYSTEMS IN THE PUBLIC SECTOR (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Financial control in the public sector plays a crucial role in ensuring the efficient use of budgetary resources and achieving governmental objectives. This paper evaluates the effectiveness of public financial control systems, with a particular focus on the mechanisms that enhance budgetary discipline, prevent misuse of funds, and improve transparency. Key methods of analysis include the examination of existing regulatory frameworks, case studies on effective financial audits, and a discussion of the challenges and opportunities faced by public financial control bodies.